Development of healthcare use across contemporary retirement pathways: results from a register based cohort study. Issue 4 (June 2022) - König, Stefanie; Kelfve, Susanne; Motel-Klingebiel, Andreas; Wetzel, Martin
Aim: We aimed to understand the interplay between retirement pathways and healthcare use in the postponed and structurally changing context of retirement. Methods: Based on Swedish register data on income and healthcare use, we applied combined sequence and cluster analysis to identify typical pathways into retirement and analysed their relation to healthcare use developments. Results: We detected five distinct pathways into retirement. Level of healthcare use was significantly higher for the pathway via disability pensions. We saw an overall increase in healthcare use across the retirement process that was related to age rather than to the different pathways. Conclusions: Level of healthcare use at the beginning of the retirement process may be related to selection into different pathways of retirement. We did not find clear evidence across several healthcare measures that different pathways lead to different developments in healthcare use.